GAMBARAN KASUS TANGGAL PREMATUR GIGI CANINUS SULUNG - Tom Christian; Renie Kumala Dewi; Amy Nindia Carabelly; Alexander Sitepu; Riky Hamdani (Dentin, 2024)
ABSTRACTBackground: Premature loss is a condition where deciduous teeth shed prematurely while replacement permanent teeth have not yet erupted. Premature loss of primary canines can be caused by caries, trauma, and systemic conditions. Maxillary canines are more prone to premature loss compared to mandibular canines. Purpose: This study aimed to determine the prevalence of premature loss of primary canine teeth among children aged 8-10 years at SDN 2 Syamsudin Noor, Landasan Ulin, Banjarbaru City in 2023. Method: This research employed an observational study with a cross-sectional design. The study included 77 students aged 8-10 years from SDN 2 Syamsudin Noor, selected using simple random sampling. Inclusion criteria were students aged 8-10 years who were cooperative respondents, with parents or guardians signing informed consent, and students in the mixed dentition phase. Exclusion criteria were students absent or sick on the day of data collection, and parents or guardians who withdrew consent. Data were collected through observational examination and filling out an odontogram. The research data were analyzed descriptively. Results: 23% of respondents experienced premature loss of primary canines, with the majority being females (66.67%). The primary canine most commonly affected was tooth element 53 (44%), and premature loss typically occurred at age 10 (38.89%). Conclusion: The description of premature loss of primary canine teeth in students at SDN 2 Syamsudin Noor aged 8-10 years, the majority of which occur in girls, namely maxillary primary canine teeth because hormonal factors at puberty can influence behavior in maintaining dental and oral hygiene.Keywords: premature loss, children, primary canines. ABSTRAKLatar Belakang: Prematur loss adalah kondisi dimana gigi desidui sudah tanggal sebelum waktunya sementara gigi permanen pengganti belum tumbuh. Prematur loss caninus sulung dapat disebabkan karena karies, trauma dan kondisi sistemik. Gigi caninus rahang atas sering mengalami tanggal prematur dibandingkan gigi caninus rahang bawah. Tujuan: Mengetahui gambaran tanggal prematur gigi caninus sulung pada anak usia 8-10 tahun di SDN 2 Syamsudin Noor Kecamatan Landasan Ulin Kota Banjarbaru pada tahun 2023. Metode: Penelitian ini merupakan penelitian observasional dengan rancangan cross sectional. Penelitian dilakukan pada siswa-siswi usia 8-10 tahun di SDN 2 Syamsudin Noor Kecamatan Landasan Ulin Kota Banjarbaru dengan teknik pengambilan sampel simple random sampling sebanyak 77 orang dengan kriteria inklusi yaitu siswa siswi berusia 8-10 tahun, kooperatif untuk menjadi responden, orang tua atau wali yang menandatangani infomed consent dan siswa siswi dalam periode gigi bercampur. Kriteria eksklusi yaitu siswa siswi yang tidak hadir atau sakit pada hari pengambilan data dan orang tua atau wali yang mengundurkan diri. Pemeriksaan dilakukan dengan observasi serta pengisian odontogram. Data hasil penelitian selanjutnya dijabarkan secara deskriptif. Hasil: Sebanyak 23% responden mengalami prematur loss caninus sulung dengan responden terbanyak adalah perempuan (66,67%) dan elemen gigi caninus sulung yang mengalami tanggal prematur terbanyak adalah gigi 53 (44%) serta tanggal prematur terbanyak pada usia 10 tahun (38,89%). Kesimpulan: Gambaran tanggal prematur gigi caninus sulung pada siswa/siswi SDN 2 Syamsudin Noor usia 8-10 tahun mayoritas terjadi pada perempuan yaitu pada gigi caninus sulung rahang atas. Hal ini karena faktor hormonal pubertas dapat memengaruhi perilaku dalam memelihara kebersihan gigi dan mulut. Kata kunci: Caninus Sulung, Anak-Anak, Premature Loss